Can Organic Amendments Override Environmental Filtering of Soil Microbiomes? Evidence From 20 Years Old Agricultural Field Trials in Contrasting Tropical Sites - Anna M. Visscher; Samuel Mathu Ndungu; Rafaela Feola Conz; Moritz Laub; Monicah Wanjiku Mucheru‐Muna; Daniel Mugendi; Rebecca Yegon; Frank Rasche; Wycliffe Waswa; Mirjam Pulleman; Bernard Vanlauwe; Johan Six; et al. (Global Change Biology, 2026)
Soil microbial communities underpin ecosystem functions critical for sustainable agriculture, yet our understanding of how long‐term management of tropical agroecosystems shapes these communities remains limited. This is particularly the case in sub‐Saharan Africa where soil health challenges are most acute for food security. Using four long‐term (~20 years) experiments across contrasting agroecological zones in Kenya, we studied how organic inputs (farmyard manure, Tithonia diversifolia , Zea mays stover; applied at 4 Mg C ha −1 year −1 ) and nitrogen fertilizer (±120 kg N ha −1 per season as calcium ammonium nitrate) affect soil microbial communities. We combined amplicon sequencing of prokaryotic (16S rRNA) and fungal (ITS2) communities with quantification of nitrogen‐cycling functional genes to examine microbial diversity, community composition, and functional potential. Site‐level edaphic properties were the main correlate of community variation, namely 30% and 28% of prokaryotic and fungal β‐diversity, respectively. Despite this strong environmental control, farmyard manure created distinguishable community patterns across all sites, significantly affecting 65 prokaryotic genera and achieving 96% reclassification success for fungal communities. Prokaryotic and fungal communities exhibited contrasting response patterns: prokaryotes responded predominantly to farmyard manure through enrichment of copiotrophic Bacillota (formerly Firmicutes), while fungi were sensitive to both farmyard manure and T. diversifolia green manure, recruiting distinct decomposer guilds based on substrate biochemistry. Functional gene responses were amplified at the driest, most nutrient‐poor site, where farmyard manure led to a 30‐fold increase in the abundance of ammonia‐oxidizing bacteria compared to the control treatment. Mineral nitrogen fertilization alone did not produce distinct community composition but modestly reduced specific nitrogen‐cycling genes. This demonstrates that organic resource management, not mineral inputs, drives long‐term microbial community development. These findings provide decadal‐scale evidence that sustained organic amendments can generate predictable microbial responses across environmentally heterogeneous tropical landscapes, informing integrated soil fertility management strategies for sub‐Saharan Africa.

Experimental evidence for grazer control of algal stable states in Florida’s spring-fed rivers - Dina M. Liebowitz; Paul Donsky; James B. Heffernan; Crystal Hartmann; Thomas K. Frazer; Matthew J. Cohen (Hydrobiologia, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

Improved procedures for the cleavage and reduction of GDGTs for hydrogen isotope analysis - C.D. Rosendahl; X. Zhao; A.E. Maloney; J.M. McFarlin; K.J. Keller; R. Kreutz; J. Altun; L.H. Bachmann; J. Hartmann; H.K. Batther; A.N. Calhoun; M. Elvert; et al. (Organic Geochemistry, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Food processing must evolve to solve global challenges - Felix Schottroff; Denise M. Mitrano; Lilia Ahrné; Elizabeth A. Ainsworth; Henry Jaeger; Eileen R. Gibney; James G. Lyng; E. Dolores O’Riordan; Huub Lelieveld; Diána Bánáti; Diana Bogueva; Anet Režek Jambrak; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Educating for groundwater sustainability in a changing world: A joint, applied, interdisciplinary and inclusive postgraduate approach - Tibor Y. Stigter; M. Teresa Condesso de Melo; Rodrigo Oliveira; Christian Bernhofer; Peter Krebs; Judith Poeschmann; Karen Rojas; Andreas Hartmann; K. Brindha (Hydrogeology Journal, 2026)
Safeguarding groundwater, a vital resource in adaptation to global change, yet increasingly under pressure, requires robust knowledge and capacity. While strong foundations in hydrogeology remain indispensable, there is a clear need for joint, interdisciplinary and applied groundwater education at the postgraduate level to address the complex and multifaceted nature of groundwater science. Building on these arguments, the Joint Master’s Programme Groundwater and Global Change was successfully launched a decade ago. This essay presents the rationale behind this approach.

RFC1-related disorders: A case series of 4-aminopyridine and acetyl-DL-leucine treatment - F. Heindl; A. Traschütz; M. Synofzik; T. Wirth; M. Anheim; A. A. Tarnutzer; A. M. Hartmann; D. Rujescu; I. Giegling; K. Feil; C. Adrion; M. Strupp (The Cerebellum, 2026)
This observational case series summarizes clinical experiences with 4-aminopyridine (4-AP) and acetyl-DL-leucine (ADLL) in patients with RFC1 -related disorders treated under named patient use conditions. Clinical data from 30 patients treated at four university centers in Germany, Switzerland, and France were analyzed. Except for three patients previously enrolled in the ALCAT randomized crossover trial, treatments were initiated as part of routine care and were not standardized for dose or duration. Analyses were based on medical records, including patient-reported outcomes and physician assessments. Four patients from Strasbourg underwent SARA and SDFS assessments before and during treatment; SARA total scores for three ALCAT participants were obtained from the original study dataset. Twelve patients received 4-AP only, seven ADLL only, and eleven both treatments at different time points. Median treatment duration was 29 days for 4-AP and 53 days for ADLL. Subjective improvement was reported in 3/22 patients (13.6%) treated with 4-AP and 3/15 (20.0%) treated with ADLL. Objective gait improvement was observed in 2/13 patients (15.4%) on 4-AP and in 2/10 (20.0%) on ADLL. No effects on downbeat nystagmus were observed. Exploratory analyses revealed no significant differences in SARA total scores between ADLL and placebo or baseline; neither SARA nor SDFS scores improved in Strasbourg patients. Responses to 4-AP and ADLL in RFC1 -related disorders were rare and limited, suggesting that neurodegenerative dysfunction of cerebellar circuits in RFC1 -disease—in contrast to certain genetic cerebellar disorders such as SCA27B—is unlikely to be improved to clinically relevant thresholds by these agents.

Enhanced bloom and pollinator diversity from native prairie restoration at a photovoltaic solar park - Yudi Li; Leslie Saul-Gershenz; Leroy J. Walston; Heidi M. Hartmann; Nicholas Tew; Joel D. Gardner; Socrates Letana; Rebecca R. Hernandez (Journal of Environmental Management, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Ten questions concerning indoor dust - Erica M. Hartmann; Karen C. Dannemiller; Delphine K. Farmer; Rachel E. O'Brien; Joseph Berberich; Jenna C. Ditto; Olivia R. Farinas; Elliott T. Gall; Anindita Ganguly; Vicki H. Grassian; Rachel Greene; Bridget Hegarty; et al. (Building and Environment, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

A sedimentary record of paleodirectional and relative paleointensity variations of the Earth's magnetic field from offshore South Brazil spanning the time from 46.15 to 5.36 ka - Camila T. Lopes; Jairo F. Savian; Everton Frigo; Gelvam A. Hartmann; Maria A.G. Pivel; Sanja Panovska; Jaime Y. Suárez-Ibarra; Caroline A. Pontel; João C. Coimbra; Sandro M. Petró; Adriana Leonhardt; Ricardo I.F. Trindade (Quaternary Science Reviews, 2025)

Application of a parsimonious large-scale distributed groundwater flow model to quantify inter-catchment groundwater flow - M. Rahman; R. Woods; F. Pianosi; T. Wagener; A. Hartmann (Journal of Hydrology, 2025)

Two-phased ITCZ-driven upper salinity stratification in the western equatorial Atlantic during Heinrich Stadial 11 - Marília C. Campos; Rodrigo A. Nascimento; Tainã M.L. Pinho; Laura Kraft; Stefano Crivellari; Svetlana Radionovskaya; Luke Skinner; Bruna B. Dias; Rodrigo C. Portilho-Ramos; Gelvam A. Hartmann; Paul A. Baker; Cleverson G. Silva; et al. (Global and Planetary Change, 2025)

The pectin puzzle: Decoding the fine structure of rhamnogalacturonan-I (RG-I) in Arabidopsis thaliana uncovers new pectin features - Liang Zhang; Jiri Vlach; Ian M. Black; Stephanie Archer-Hartmann; Christian Heiss; Parastoo Azadi; Breeanna R. Urbanowicz (Carbohydrate Polymers, 2025)

Divergent Trends in Insect Disturbance Across Europe's Temperate and Boreal Forests - Tomáš Hlásny; Roman Modlinger; Jostein Gohli; Rupert Seidl; Paal Krokene; Iris Bernardinelli; Simon Blaser; Gediminas Brazaitis; Gailenė Brazaitytė; Eckehard G. Brockerhoff; György Csóka; Laura Dobor; et al. (Global Change Biology, 2025)
Ongoing shifts in climate and land use have altered interactions between trees and insect herbivores, changing biotic disturbance regimes. However, as these changes are complex and vary across host species, insect taxa, and feeding guilds, they remain poorly understood. We compiled annual records of forest insect disturbance from 15 countries in temperate and boreal Europe, spanning the period from 2000 to 2022. The dataset comprises 1361 time series characterizing the dynamics of 50 herbivorous insects. We used this dataset to test whether insect disturbance has systematically changed during the 23‐year period across host trees and feeding guilds, whether it varies along latitudinal and climatic gradients, and whether synchrony exists among species in the same guild or among species sharing the same host. Since 2000, borer disturbance was predominantly concentrated on gymnosperms, while defoliators impacted gymnosperms and angiosperms more evenly. While 85.8% of gymnosperm disturbance was inflicted by a single species, Ips typographus , the majority of disturbances to angiosperms were caused by six different species. Borer impact on gymnosperms has increased in the 21st century, while defoliator impact has decreased across both clades. In contrast to diverging temporal trends, disturbance was consistently greater in warmer and drier conditions across feeding guilds and host types. We identified significant synchrony in insect disturbance within host types and feeding guilds but not between these groups, suggesting shared drivers within guilds and host types. Increasing insect disturbance to gymnosperms may catalyze adaptive transformations in Europe's forests, promoting a shift from historical conifer‐dominated management to broadleaved trees, which are less affected by insect herbivores. Our findings reveal a diversity of trends in insect herbivory, underscoring the need to strengthen monitoring and research in order to better understand underlying mechanisms and identify emerging threats that may not be apparent in currently available data.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Research directions in thermoregulation during exercise in extreme environments - J.I. Priego-Quesada; M. Gil-Calvo; T. Mundel; T. Hartmann; F.E. Marino (Journal of Thermal Biology, 2025)

Effect of the glucagon-like peptide-1 (GLP-1) receptor agonist semaglutide on alcohol consumption in alcohol-preferring male vervet monkeys - Anders Fink-Jensen; Gitta Wörtwein; Mette Kruse Klausen; Jens Juul Holst; Bolette Hartmann; Morgan Thomsen; Maurice Ptito; Amy Beierschmitt; Roberta M. Palmour (Psychopharmacology, 2025)
Rationale Glucagon-like peptide-1 (GLP-1) receptor agonists reduce alcohol consumption in rodents and non-human primates. Semaglutide is a new long-acting GLP-1 receptor agonist, widely used in the clinic against type 2 diabetes and obesity. It is also reported to reduce alcohol intake in rodents. Objectives This study investigates the possible inhibitory effect of semaglutide on alcohol intake in alcohol-preferring African green monkeys. Methods We performed a vehicle-controlled study on male monkeys that had demonstrated a preference for alcohol. In the monkeys selected for voluntary alcohol drinking, alcohol consumption was measured for ten days at baseline (Monday to Friday for two weeks). During this period, the monkeys had access to alcohol 4 h per day and free access to water 24 h per day. After two weeks of baseline measurements, the monkeys were randomized to semaglutide or vehicle. Each group consisted of ten monkeys, and the two groups were balanced with respect to baseline alcohol intake. Following the baseline period, the monkeys were treated with escalating doses of semaglutide (up to 0.05 mg/kg) or vehicle subcutaneously twice weekly for two weeks during which period alcohol was not available. After uptitration, the monkeys had access to alcohol 4 h daily for 20 days (Monday to Friday for 4 weeks), and alcohol consumption was measured. During this alcohol exposure period, treatment with semaglutide (0.05 mg/kg twice weekly) or vehicle continued for three weeks followed by a one-week washout period. Results Compared to the vehicle, semaglutide significantly reduced alcohol intake. There were no signs of emetic events or changes in water intake. Conclusions These data demonstrate for the first time the potent effect of semaglutide in reducing voluntary alcohol intake in non-human primates and further substantiate the need for clinical trials investigating the effect of semaglutide in patients with alcohol-use disorder.

The time for ambitious action is now: Science-based recommendations for plastic chemicals to inform an effective global plastic treaty - Susanne M. Brander; Kala Senathirajah; Marina O. Fernandez; Judith S. Weis; Eva Kumar; Annika Jahnke; Nanna B. Hartmann; Juan José Alava; Trisia Farrelly; Bethanie Carney Almroth; Ksenia J. Groh; Kristian Syberg; et al. (Science of The Total Environment, 2024)

Thyroid lesions in a population of domestic cats submitted to necropsy without clinical suspicion of thyroid disease - Alana P. Herbichi; Douglas M. Lorenzetti; Matheus Y. dos Santos; Gabriela Hartmann; Rafael A. Fighera; Mariana M. Flores (Journal of Comparative Pathology, 2024)

Collision-induced absorptions by pure CO2 in the infrared: New measurements in the 1150–4500 cm−1 spectral range and empirical modeling for applications - H. Tran; J.M. Hartmann; E. Rambinison; M. Turbet (Icarus, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

P19-29 Trifloxystrobin – combination of in vivo and in vitro approaches to address Parkinson disease concerns - K. Bothe; A. Farhi; C. Hilmi; K. Tilmant; E. Hallscheidt; M. Hahn; M. Lamshoeft; K. Hartmann (Toxicology Letters, 2024)

Partitioning the influence of host specificity in amphibian populations threatened by multiple emerging infectious diseases - Arik M. Hartmann; Kimberly Sash; E. Pierson Hill; Natalie M. Claunch; Max L. Maddox; Sarah McGrath-Blaser; Cory C. McKinstry; Robert J. Ossiboff; Ana V. Longo (Biological Conservation, 2024)

Anomalies identification in Smart Water Metering Networks: Fostering improved water efficiency - Maria Nelago Kanyama; Fungai Bhunu Shava; Attle M Gamundani; Andreas Hartmann (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

High ammonia loading rate and biofilm reattachment initiated partial nitrification and anammox in a membrane aerated biofilm reactor - Jiang-Feng Zhang; Chun-Yu Lai; Xiao-Xin Cao; Erica M. Hartmann; He-Ping Zhao (Journal of Water Process Engineering, 2024)

Use of Cognitive and Behavioral Strategies During a Weight Loss Program: A Secondary Analysis of the Doctor Referral of Overweight People to Low-Energy Total Diet Replacement Treatment (DROPLET) Trial - John Aaron Henry; Nerys M. Astbury; Jamie Hartmann-Boyce; Constantinos Koshiaris; Susan A. Jebb (Journal of the Academy of Nutrition and Dietetics, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Conserved worker policing in African carpenter ants with drastically different egg chemotypes - Jan Buellesbach; Janina Rinke; Leonie Reuter; Jurian M. Thomas; Vivien Hartmann; Marius Pohl; Jürgen Gadau; Ulrich R. Ernst (Evolutionary Ecology, 2023)
Distinctive chemical signatures have the potential to serve as discriminatory cues for olfactory recognition mechanisms. Cuticular hydrocarbon (CHC) profiles are among the most prominent chemical signatures in insects that can be highly diverse even among closely related species and between populations with similar ecology. Particularly within the major insect order Hymenoptera, CHC profiles are characterized by high complexity and variation with the potential to evolve rapidly. In this study, we found two very distinct CHC chemotypes distinguishing sympatric colonies of the African carpenter ant Camponotus maculatus (Hymenoptera: Formicinae). These chemotypic differences were mainly detected on the surface profiles of eggs produced by either queens or isolated worker groups. In one chemotype, queen- and worker-laid eggs are very similar. This is largely contrasted by the other chemotype, where queen-laid eggs clearly differ from worker-laid eggs with several prominent queen-exclusive compounds. However, workers display a stable behavior of discriminating against and selectively disposing of worker-laid eggs i.e., worker policing, independent of egg chemotype. Furthermore, genetic barcoding of workers revealed a clear separation between colonies characterized by producing these two distinct egg chemotypes, which may indicate that these colonies belong to a cryptic species complex. Interestingly, worker policing behaviour appears to be evolutionarily conserved, despite the strikingly different egg surface profiles.

P16-33: Identifying and characterizing toxicity liabilities of pharmaceuticals using ToxProfiler: A blinded case study with the ITLF consortium - B. Ter Braak; L. Wolters; K. Elbertse; M. Beilmann; H. Boonen; A. Doherty; F. Van Goethem; P. Hewitt; J. Hornberg; J. Koch; S. Kusterman; J. Lyon; et al. (Toxicology Letters, 2023)

Mitigation of antimicrobial resistance genes in greywater treated at household level - Weitao Shuai; Daniella Itzhari; Zeev Ronen; Erica M. Hartmann (Science of The Total Environment, 2023)

Ambient and substrate energy influence decomposer diversity differentially across trophic levels - Peter Kriegel; Sebastian Vogel; Romain Angeleri; Petr Baldrian; Werner Borken; Christophe Bouget; Antoine Brin; Heinz Bussler; Cristiana Cocciufa; Benedikt Feldmann; Martin M. Gossner; Elena Haeler; et al. (Ecology Letters, 2023)
The species‐energy hypothesis predicts increasing biodiversity with increasing energy in ecosystems. Proxies for energy availability are often grouped into ambient energy (i.e., solar radiation) and substrate energy (i.e., non‐structural carbohydrates or nutritional content). The relative importance of substrate energy is thought to decrease with increasing trophic level from primary consumers to predators, with reciprocal effects of ambient energy. Yet, empirical tests are lacking. We compiled data on 332,557 deadwood‐inhabiting beetles of 901 species reared from wood of 49 tree species across Europe. Using host‐phylogeny‐controlled models, we show that the relative importance of substrate energy versus ambient energy decreases with increasing trophic levels: the diversity of zoophagous and mycetophagous beetles was determined by ambient energy, while non‐structural carbohydrate content in woody tissues determined that of xylophagous beetles. Our study thus overall supports the species‐energy hypothesis and specifies that the relative importance of ambient temperature increases with increasing trophic level with opposite effects for substrate energy.

Intensity of sample processing methods impacts wastewater SARS-CoV-2 whole genome amplicon sequencing outcomes - Shuchen Feng; Sarah M. Owens; Abhilasha Shrestha; Rachel Poretsky; Erica M. Hartmann; George Wells (Science of The Total Environment, 2023)

Prevalence of effective fisheries management in a developed nation and its link to stock sustainability - Nicholas J. Hill; Malcolm Haddon; Klaas Hartmann; L. Richard Little; Jeremy M. Lyle; Bradley R. Moore; Simon Nicol (Marine Policy, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Assessment of the interactions between pea and salivary proteins in aqueous dispersions - M. Assad-Bustillos; A.C. Cázares-Godoy; M. Devezeaux de Lavergne; C. Schmitt; C. Hartmann; E. Windhab (Innovative Food Science & Emerging Technologies, 2023)

A micromechanical based finite element model approach to accurately predict the effective thermal properties of micro-aerated chocolate - D. Bikos; G. Samaras; M.N. Charalambides; P. Cann; M. Masen; C. Hartmann; J. Vieira; A. Sergis; Y. Hardalupas (Innovative Food Science & Emerging Technologies, 2023)

Carbon tax salience counteracts price effects through moral licensing - Patrick Hartmann; Aitor Marcos; Jose M. Barrutia (Global Environmental Change, 2023)

Heterotrophic denitrification: An overlooked factor that contributes to nitrogen removal in n-DAMO mixed culture - Xu Guo; Chun-Yu Lai; Erica M. Hartmann; He-Ping Zhao (Environmental Research, 2023)

Decision support for the Ecosystem-Based Management of a Range-Extending Species in a Global Marine Hotspot Presents Effective Strategies and Challenges - Lucy M. Robinson; Martin P. Marzloff; Ingrid van Putten; Gretta Pecl; Sarah Jennings; Sam Nicol; Alistair J. Hobday; Sean Tracey; Klaas Hartmann; Marcus Haward; Stewart Frusher (Ecosystems, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Benzalkonium chloride: A systematic review of its environmental entry through wastewater treatment, potential impact, and mitigation strategies - Olivia Williams Barber; Erica M. Hartmann (Critical Reviews in Environmental Science and Technology, 2022)

Euphrasia ultima , a new locally endemic diploid species from the Ortler/Ortles range (Italy), is a close relative of widespread allotetraploid E. minima - Julia Hartmann; Lisa Silbernagl; Gerald M. Schneeweiss; Michael H. J. Barfuss; Hanna Weiss-Schneeweiss; Peter Schönswetter (Plant Biosystems, 2022)

The β-Secretase Substrate Seizure 6–Like Protein (SEZ6L) Controls Motor Functions in Mice - Emma Ong-Pålsson; Jasenka Rudan Njavro; Yvette Wilson; Martina Pigoni; Andree Schmidt; Stephan A. Müller; Michael Meyer; Jana Hartmann; Marc Aurel Busche; Jenny M. Gunnersen; Kathryn M. Munro; Stefan F. Lichtenthaler (Molecular Neurobiology, 2022)
The membrane protein seizure 6–like (SEZ6L) is a neuronal substrate of the Alzheimer’s disease protease BACE1, and little is known about its physiological function in the nervous system. Here, we show that SEZ6L constitutive knockout mice display motor phenotypes in adulthood, including changes in gait and decreased motor coordination. Additionally, SEZ6L knockout mice displayed increased anxiety-like behaviour, although spatial learning and memory in the Morris water maze were normal. Analysis of the gross anatomy and proteome of the adult SEZ6L knockout cerebellum did not reveal any major differences compared to wild type, indicating that lack of SEZ6L in other regions of the nervous system may contribute to the phenotypes observed. In summary, our study establishes physiological functions for SEZ6L in regulating motor coordination and curbing anxiety-related behaviour, indicating that aberrant SEZ6L function in the human nervous system may contribute to movement disorders and neuropsychiatric diseases.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Red seaweeds strengthening the nexus between nutrition and health: phytochemical characterization and bioactive properties of Grateloupia turuturu and Porphyra umbilicalis extracts - João Ferreira; Anja Hartmann; Carlos Martins-Gomes; Fernando M. Nunes; Eliana B. Souto; Dario L. Santos; Helena Abreu; Rui Pereira; Mário Pacheco; Isabel Gaivão; Amélia M. Silva (Journal of Applied Phycology, 2021)

Spatial asymmetries (“pseudoneglect”) in free visual exploration—modulation of age and relationship to line bisection - Kathrin Chiffi; Lorenzo Diana; Matthias Hartmann; Dario Cazzoli; Claudio L. Bassetti; René M. Müri; Aleksandra K. Eberhard-Moscicka (Experimental Brain Research, 2021)
When humans visually explore an image, they typically tend to start exploring its left side. This phenomenon, so-called pseudoneglect, is well known, but its time-course has only sparsely been studied. Furthermore, it is unclear whether age influences pseudoneglect, and the relationship between visuo-spatial attentional asymmetries in a free visual exploration task and a classical line bisection task has not been established. To address these questions, 60 healthy participants, aged between 22 and 86, were assessed by means of a free visual exploration task with a series of naturalistic, colour photographs of everyday scenes, while their gaze was recorded by means of a contact-free eye-tracking system. Furthermore, a classical line bisection task was administered, and information concerning handedness and subjective alertness during the experiment was obtained. The results revealed a time-sensitive window during visual exploration, between 260 and 960 ms, in which age was a significant predictor of the leftward bias in gaze position, i.e., of pseudoneglect. Moreover, pseudoneglect as assessed by the line bisection task correlated with the average gaze position throughout a time-window of 300–1490 ms during the visual exploration task. These results suggest that age influences visual exploration and pseudoneglect in a time-sensitive fashion, and that the degree of pseudoneglect in the line bisection task correlates with the average gaze position during visual exploration in a time-sensitive manner.

Retraction Note to: Structured Decision-Making Identifies Effective Strategies and Potential Barriers for Ecosystem-Based Management of a Range-Extending Species in a Global Marine Hotspot - Lucy M. Robinson; Martin P. Marzloff; Ingrid van Putten; Gretta Pecl; Sarah Jennings; Sam Nicol; Alistair J. Hobday; Sean Tracey; Klaas Hartmann; Marcus Haward; Stewart Frusher (Ecosystems, 2021)

Cypermethrin- and fipronil-based insecticides cause biochemical changes in Physalaemus gracilis tadpoles - Camila F. Rutkoski; Natani Macagnan; Alexandre Folador; Vrandrieli J. Skovronski; Aline M. B. do Amaral; Jossiele Wesz Leitemperger; Maiara Dorneles Costa; Paulo A. Hartmann; Caroline Müller; Vania L. Loro; Marilia T. Hartmann (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Setting the stage for next-generation risk assessment with non-animal approaches: the EU-ToxRisk project experience - M. J. Moné; G. Pallocca; S. E. Escher; T. Exner; M. Herzler; S. Hougaard Bennekou; H. Kamp; E. D. Kroese; Marcel Leist; T. Steger-Hartmann; B. van de Water (Archives of Toxicology, 2020)
In 2016, the European Commission launched the EU-ToxRisk research project to develop and promote animal-free approaches in toxicology. The 36 partners of this consortium used in vitro and in silico methods in the context of case studies (CSs). These CSs included both compounds with a highly defined target (e.g. mitochondrial respiratory chain inhibitors) as well as compounds with poorly defined molecular initiation events (e.g. short-chain branched carboxylic acids). The initial project focus was on developing a science-based strategy for read-across (RAx) as an animal-free approach in chemical risk assessment. Moreover, seamless incorporation of new approach method (NAM) data into this process (= NAM-enhanced RAx) was explored. Here, the EU-ToxRisk consortium has collated its scientific and regulatory learnings from this particular project objective. For all CSs, a mechanistic hypothesis (in the form of an adverse outcome pathway) guided the safety evaluation. ADME data were generated from NAMs and used for comprehensive physiological-based kinetic modelling. Quality assurance and data management were optimized in parallel. Scientific and Regulatory Advisory Boards played a vital role in assessing the practical applicability of the new approaches. In a next step, external stakeholders evaluated the usefulness of NAMs in the context of RAx CSs for regulatory acceptance. For instance, the CSs were included in the OECD CS portfolio for the Integrated Approach to Testing and Assessment project. Feedback from regulators and other stakeholders was collected at several stages. Future chemical safety science projects can draw from this experience to implement systems toxicology-guided, animal-free next-generation risk assessment.

First record of the mating behaviour of the spotted surubim Pseudoplatystoma corruscans in the Uruguay River - Lucas A. Pachla; Paula B. Hartmann; Marthoni V. Massaro; Rodrigo Bastian; Fernando M. Pelicice; David A. Reynalte‐Tataje (Journal of Fish Biology, 2020)
The spotted surubim Pseudoplatystoma corruscans is a large migratory catfish native to the La Plata and San Francisco basins. Nonetheless, its reproductive dynamics and behaviour remain poorly understood. This brief note provides the first record of the mating behaviour of P. corruscans in natural conditions. This behaviour was observed in the main channel of the Middle Uruguay River (Brazil). A school of approximately 25 fish, 5 females (with protruding abdomen and larger body size) and 20 males, were followed and videotaped. The largest female led the school, followed by other fish. Some males disputed repeatedly the posterior region of the females, whereas other males continuously repelled them. Eventually, some males, apparently exhausted, floated belly up. During this event, males were in a state of pronounced agitation, and some had abrasions in the head. Polygamy characterized the mating behaviour of P. corruscans .

A Variation in FGF14 Is Associated with Downbeat Nystagmus in a Genome-Wide Association Study - Michael Strupp; Stephan Maul; Bettina Konte; Annette M. Hartmann; Ina Giegling; Sophia Wollenteit; Katharina Feil; Dan Rujescu (The Cerebellum, 2020)
Downbeat nystagmus (DBN) is a frequent form of acquired persisting central fixation nystagmus, often associated with other cerebellar ocular signs, such as saccadic smooth pursuit or gaze-holding deficits. Despite its distinct clinical features, the underlying etiology of DBN often remains unclear. Therefore, a genome-wide association study (GWAS) was conducted in 106 patients and 2609 healthy controls of European ancestry to identify genetic variants associated with DBN. A genome-wide significant association ( p < 5 × 10 −8 ) with DBN was found for a variation on chromosome 13 located within the fibroblast growth factor 14 gene (FGF14). FGF14 is expressed in Purkinje cells (PCs) and a reduction leads to a decreased spontaneous firing rate and excitability of PCs, compatible with the pathophysiology of DBN. In addition, mutations in the FGF14 gene cause spinocerebellar ataxia type 27. Suggestive associations ( p < 1 × 10 −05 ) could be detected for 15 additional LD-independent loci, one of which is also located in the FGF14 gene. An association of a region containing the dihydrofolate reductase (DHFR) and MutS Homolog 3 (MSH3) genes on chromosome 5 was slightly below the genome-wide significance threshold. DHFR is relevant for neuronal regulation, and a dysfunction is known to induce cerebellar damage. Among the remaining twelve suggestive associations, four genes (MAST4, TPPP, FTMT, and IDS) seem to be involved in cerebral pathological processes. Thus, this GWAS analysis has identified a potential genetic contribution to idiopathic DBN, including suggestive associations to several genes involved in postulated pathological mechanisms of DBN (i.e., impaired function of cerebellar PCs).

Beneficial microorganisms in agriculture: the future of plant growth-promoting rhizobacteria - Veronica M. Reis; Bruno J. R. Alves; Anton Hartmann; Euan K. James; Jerri E. Zilli (Plant and Soil, 2020)

Two new species in a new genus and a critical revision of Brachybasidiaceae (Exobasidiales, Basidiomycota) in honor of Franz Oberwinkler - M. Piepenbring; M. Hartmann; T. A. Hofmann; M. Lutz (Mycological Progress, 2020)
The Brachybasidiaceae are a family of 22 known species of plant-parasitic microfungi belonging to Exobasidiales, Basidiomycota. Within this family, species of the largest genus Kordyana develop balls of basidia on top of stomatal openings. Basidial cells originate from fungal stroma filling substomatal chambers. Species of Kordyana typically infect species of Commelinaceae. During fieldwork in the neotropics, fungi morphologically similar to Kordyana spp. were found on Goeppertia spp. (syn. Calathea spp., Marantaceae), namely on G. panamensis in Panama and on G. propinqua in Bolivia. These specimens are proposed as representatives of a genus new to science, Marantokordyana , based on the distinct host family and molecular sequence data of ITS and LSU rDNA regions. The specimens on the two host species represent two species new to science, M. oberwinkleriana on G. panamensis and M. boliviana on G. propinqua . They differ by the size and shape of their basidia, molecular sequence data of ITS and LSU rDNA regions, and host plant species. In the past, the understanding of Brachybasidiaceae at order and family level was significantly improved by investigation realized by Franz Oberwinkler and his collaborators at the University of Tübingen, Germany. On species level, however, our knowledge is still very poor due to incomplete species descriptions of several existing names in literature, scarceness of specimens, as well as sequence data lacking for many taxa and for further barcode regions. Especially species of Kordyana and species of Dicellomyces are in need of revision.

Defective interferon priming and impaired antiviral responses in a patient with an IRF7 variant and severe influenza - Michelle M. Thomsen; Sofie E. Jørgensen; Hans Henrik Gad; Merete Storgaard; Jakob Gjedsted; Mette Christiansen; Rune Hartmann; Trine H. Mogensen (Medical Microbiology and Immunology, 2019)

Toxic effects of pyrethroids in tadpoles of Physalaemus gracilis (Anura: Leptodactylidae) - Guilherme V. Vanzetto; Jéssica G. Slaviero; Paola F. Sturza; Camila F. Rutkoski; Natani Macagnan; Cassiane Kolcenti; Paulo A. Hartmann; Claudia M. Ferreira; Marilia T. Hartmann (Ecotoxicology, 2019)

Advancing our understanding of the connectivity, evolution and management of marine lobsters through genetics - Catarina N. S. Silva; Cecilia Villacorta-Rath; Laura N. Woodings; Nicholas P. Murphy; Bridget S. Green; Klaas Hartmann; Caleb Gardner; James J. Bell; Jan M. Strugnell (Reviews in Fish Biology and Fisheries, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Microclimate Influences Mangrove Freeze Damage: Implications for Range Expansion in Response to Changing Macroclimate - Michael J. Osland; Arik M. Hartmann; Richard H. Day; Michael S. Ross; Courtney T. Hall; Laura C. Feher; William C. Vervaeke (Estuaries and Coasts, 2019)

Prediction of human drug-induced liver injury (DILI) in relation to oral doses and blood concentrations - Wiebke Albrecht; Franziska Kappenberg; Tim Brecklinghaus; Regina Stoeber; Rosemarie Marchan; Mian Zhang; Kristina Ebbert; Hendrik Kirschner; Marianna Grinberg; Marcel Leist; Wolfgang Moritz; Cristina Cadenas; et al. (Archives of Toxicology, 2019)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Biophysical drivers of coral trophic depth zonation - Gareth J. Williams; Stuart A. Sandin; Brian J. Zgliczynski; Michael D. Fox; Jamison M. Gove; Justin S. Rogers; Kathryn A. Furby; Aaron C. Hartmann; Zachary R. Caldwell; Nichole N. Price; Jennifer E. Smith (Marine Biology, 2018)

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Porites coral response to an oceanographic and human impact gradient in the Line Islands - Jessica E. Carilli; Aaron C. Hartmann; Scott F. Heron; John M. Pandolfi; Kim Cobb; Hussein Sayani; Robert Dunbar; Stuart A. Sandin (Limnology and Oceanography, 2017)
Coral bleaching caused by heat stress (warm water) will arguably be the greatest driver of coral reef loss in the coming decades. Understanding how corals have adapted to distinct oceanographic regimes on multiple scales can provide insight into future tolerance and persistence, information critical to directed intervention or targeted protections. The northern Line Islands span a gradient in oceanographic regimes across latitudes, with seawater becoming warmer, fresher, more oligotrophic, and more saturated with aragonite away from the equator. The combination of this regional gradient and island‐scale (local) conditions was used as a natural experiment against which to test how massive Porites corals respond to these background conditions and episodic heat stress. We found that coral condition, represented by a metric combining tissue thickness, lipids, and calcification, was similar at almost all islands, though there were differences in how corals allocate resources among these biological parameters. Corals at Teraina, the most densely inhabited island, showed evidence for reduced calcification, potentially associated with human impacts and/or outflow of freshwater from the island. In contrast, Porites corals at Palmyra, a wildlife reserve, exhibited unexpectedly high tissue‐condition metrics for its latitude, suggesting an additional food source, possibly plankton‐rich lagoonal outflow. We did not find a strong relationship between human habitation and the response of Porites corals to recent heat stress. However, differences in coral calcification rates and energy stores between observed values and those expected based solely on the regional oceanographic gradient, suggests local effects have indirect impacts on these corals.

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

The Fate of Carbon in Sediments of the Xingu and Tapajós Clearwater Rivers, Eastern Amazon - Dailson J. Bertassoli; André O. Sawakuchi; Henrique O. Sawakuchi; Fabiano N. Pupim; Gelvam A. Hartmann; Michael M. McGlue; Cristiano M. Chiessi; Matthias Zabel; Enno Schefuß; Tatiana S. Pereira; Rudney A. Santos; Samantha B. Faustino; et al. (Frontiers in Marine Science, 2017)

Current insights into the sulfatase pathway in human testis and cultured Sertoli cells - K. Hartmann; J. Bennien; B. Wapelhorst; K. Bakhaus; V. Schumacher; S. Kliesch; W. Weidner; M. Bergmann; J. Geyer; D. Fietz (Histochemistry and Cell Biology, 2016)

Expanding the concept of sustainable seafood using Life Cycle Assessment - Friederike Ziegler; Sara Hornborg; Bridget S Green; Ole Ritzau Eigaard; Anna K Farmery; Linus Hammar; Klaas Hartmann; Sverker Molander; Robert W R Parker; Erik Skontorp Hognes; Ian Vázquez‐Rowe; Anthony D M Smith (Fish and Fisheries, 2016)
Fisheries management and sustainability assessment of fisheries more generally have recently expanded their scope from single‐species stock assessment to ecosystem‐based approaches, aiming to incorporate economic, social and local environmental impacts, while still excluding global‐scale environmental impacts. In parallel, Life Cycle Assessment ( LCA ) has emerged as a widely used and recommended framework to assess environmental impacts of products, including global‐scale impacts. For over a decade, LCA has been applied to seafood supply chains, leading to new insights into the environmental impact of seafood products. We present insights from seafood LCA research with particular focus on evaluating fisheries management, which strongly influences the environmental impact of seafood products. Further, we suggest tangible ways in which LCA could be taken up in management. By identifying trade‐offs, LCA can be a useful decision support tool and avoids problem shifting from one concern (or activity) to another. The integrated, product‐based and quantitative perspective brought by LCA could complement existing tools. One example is to follow up fuel use of fishing, as the production and combustion of fuel used dominates overall results for various types of environmental impacts of seafood products, and is also often linked to biological impacts of fishing. Reducing the fuel use of fisheries is therefore effective to reduce overall impacts. Allocating fishing rights based on environmental performance could likewise facilitate the transition to low‐impact fisheries. Taking these steps in an open dialogue between fishers, managers, industry, NGO s and consumers would enable more targeted progress towards sustainable fisheries.

QTL mapping and breeding value estimation through pedigree-based analysis of fruit size and weight in four diverse peach breeding programs - Jonathan Fresnedo-Ramírez; Terrence J. Frett; Paul J. Sandefur; Alejandra Salgado-Rojas; John R. Clark; Ksenija Gasic; Cameron P. Peace; Natalie Anderson; Timothy P. Hartmann; David H. Byrne; Marco C. A. M. Bink; Eric van de Weg; et al. (Tree Genetics & Genomes, 2016)

Antifungal prophylaxis with posaconazole vs. fluconazole or itraconazole in pediatric patients with neutropenia - M. Döring; M. Eikemeier; K. M. Cabanillas Stanchi; U. Hartmann; M. Ebinger; C.-P. Schwarze; A. Schulz; R. Handgretinger; I. Müller (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Occupational kneeling and squatting: development and validation of an assessment method combining measurements and diaries - Dirk M. Ditchen; Rolf P. Ellegast; Tom Gawliczek; Bernd Hartmann; Monika A. Rieger (International Archives of Occupational and Environmental Health, 2015)

Quantifying the sensitivity of ephemeral streams to land disturbance activities in arid ecosystems at the watershed scale - Ben L. O’Connor; Yuki Hamada; Esther E. Bowen; Mark A. Grippo; Heidi M. Hartmann; Terri L. Patton; Robert A. Van Lonkhuyzen; Adrianne E. Carr (Environmental Monitoring and Assessment, 2014)

Uptake and depuration of gold nanoparticles in Daphnia magna - L. M. Skjolding; K. Kern; R. Hjorth; N. Hartmann; S. Overgaard; G. Ma; J. G. C. Veinot; A. Baun (Ecotoxicology, 2014)

Isolation and characterization of eight microsatellite loci in the brook lamprey Lampetra planeri (Petromyzontiformes) using 454 sequence data - I. M. Schedina; S. Pfautsch; S. Hartmann; N. Dolgener; A. Polgar; P. G. Bianco; R. Tiedemann; V. Ketmaier (Journal of Fish Biology, 2014)
Eight polymorphic microsatellite loci were developed for the brook lamprey Lampetra planeri through 454 sequencing and their usefulness was tested in 45 individuals of both L. planeri and the river lamprey Lampetra fluviatilis . The number of alleles per loci ranged between two and five; the Italian and Irish populations had a mean expected heterozygosity of 0·388 and 0·424 and a mean observed heterozygosity of 0·418 and 0·411, respectively.

Comparison of itraconazole, voriconazole, and posaconazole as oral antifungal prophylaxis in pediatric patients following allogeneic hematopoietic stem cell transplantation - M. Döring; O. Blume; S. Haufe; U. Hartmann; A. Kimmig; C.-P. Schwarze; P. Lang; R. Handgretinger; I. Müller (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Shotgun proteomics suggests involvement of additional enzymes in dioxin degradation by S phingomonas wittichii RW1 - Erica M. Hartmann; Jean Armengaud (Environmental Microbiology, 2014)
Summary Chlorinated congeners of dibenzo‐ p ‐dioxin and dibenzofuran are widely dispersed pollutants that can be treated using microorganisms, such as the S phingomonas wittichii RW1 bacterium, able to transform some of them into non‐toxic substances. The enzymes of the upper pathway for dibenzo‐ p ‐dioxin degradation in S . wittichii RW1 have been biochemically and genetically characterized, but its genome sequence indicated the existence of a tremendous potential for aromatic compound transformation, with 56 ring‐hydroxylating dioxygenase subunits, 34 extradiol dioxygenases and 40 hydrolases. To further characterize this enzymatic arsenal, new methodological approaches should be employed. Here, a large shotgun proteomic survey was performed on cells grown on dibenzofuran, dibenzo‐ p ‐dioxin and 2‐chlorodibenzo‐ p ‐dioxin, and compared with growth on acetate. Changes in the proteome were monitored over time. In total, 502 proteins were observed and quantified using a label‐free mass spectrometry‐based approach; all data were deposited to the P roteome X change ( PXD 000403). Our results confirmed the roles of the dioxin dioxygenase DxnA1A2 , trihydroxybiphenyl dioxygenase DbfB , meta ‐cleavage product hydrolase DxnB and reductase RedA2 , and corroborated the proposed involvement of the S wit_3046 dioxygenase and DxnB2 hydrolase. Trends across substrates and over the course of growth do not support concerted pathway regulation and suggest the involvement of an additional hydrolase and several TonB ‐dependent receptors.

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

A novel method for the identification of synchronization effects in multichannel ECoG with an application to epilepsy - A. Graef; M. Hartmann; C. Flamm; C. Baumgartner; M. Deistler; T. Kluge (Biological Cybernetics, 2013)

Self-motion perception training: thresholds improve in the light but not in the dark - Matthias Hartmann; Sarah Furrer; Michael H. Herzog; Daniel M. Merfeld; Fred W. Mast (Experimental Brain Research, 2013)

Validity of self-reports of knee-straining activities at work: a field study with 6-month follow-up - Dirk M. Ditchen; Rolf P. Ellegast; Bernd Hartmann; Monika A. Rieger (International Archives of Occupational and Environmental Health, 2013)

Molecular characterisation of the diazotrophic bacterial community in uninoculated and inoculated field-grown sugarcane (Saccharum sp.) - Doreen Fischer; Barbara Pfitzner; Michael Schmid; Jean L. Simões-Araújo; Veronica M. Reis; William Pereira; Ernesto Ormeño-Orrillo; Brigitte Hai; Andreas Hofmann; Michael Schloter; Esperanza Martinez-Romero; Jose Ivo Baldani; et al. (Plant and Soil, 2012)

Cholinergic chemosensory cells in the auditory tube - G. Krasteva; P. Hartmann; T. Papadakis; M. Bodenbenner; L. Wessels; E. Weihe; B. Schütz; A. C. Langheinrich; V. Chubanov; T. Gudermann; I. Ibanez-Tallon; W. Kummer (Histochemistry and Cell Biology, 2012)

Excretion of 2,3-dihydroxy-propionamide (OH-PA), the hydrolysis product of glycidamide, in human urine after single oral dose of deuterium-labeled acrylamide - Eva C. Hartmann; Julia M. Latzin; Birgit K. Schindler; Holger M. Koch; Jürgen Angerer (Archives of Toxicology, 2011)

Lack of association between 71 variations located in candidate genes and response to acute haloperidol treatment - Ina Giegling; Antonio Drago; Martin Schäfer; Annette M. Hartmann; Thomas Sander; Mohammad Reza Toliat; Hans-Jürgen Möller; Diana De Ronchi; Hans H. Stassen; Dan Rujescu; Alessandro Serretti (Psychopharmacology, 2011)

Multiple accretion at the eastern margin of the Rio de la Plata craton: the prolonged Brasiliano orogeny in southernmost Brazil - K. Saalmann; A. Gerdes; Y. Lahaye; L. A. Hartmann; M. V. D. Remus; A. Läufer (International Journal of Earth Sciences, 2011)

Susceptibility of European cultivars of Italian and perennial ryegrass to crown and stem rust - F. X. Schubiger; J. Baert; B. Bayle; P. Bourdon; B. Cagas; V. Cernoch; E. Czembor; F. Eickmeyer; U. Feuerstein; S. Hartmann; H. Jakesova; D. Johnston; et al. (Euphytica, 2010)

N-Acetyl-S-(1-carbamoyl-2-hydroxy-ethyl)-l-cysteine (iso-GAMA) a further product of human metabolism of acrylamide: comparison with the simultaneously excreted other mercaptuic acids - Eva C. Hartmann; Melanie I. Boettcher; Hermann M. Bolt; Hans Drexler; Jürgen Angerer (Archives of Toxicology, 2009)

Ringtest zum Nachweis von ZNS in Fleischerzeugnissen - C. Krex; F. Hartmann; M. Grießbach; W. Biedermann; U. Truyen; E. Lücker (Journal of Consumer Protection and Food Safety, 2009)

Reproductive biology and implications for management of the orange‐spotted grouper Epinephelus coioides in the southern Arabian Gulf - E. M. Grandcourt; T. Z. Al Abdessalaam; F. Francis; A. T. Al Shamsi; S. A. Hartmann (Journal of Fish Biology, 2009)
The reproductive biology of Epinephelus coioides was determined from the examination of 1455 individuals collected between July 2005 and June 2007 in the southern Arabian Gulf. Histological preparations of gonads indicated that males were either derived from a juvenile phase or the transition of postspawning females, confirming a diandric protogynous sexual pattern. The spawning season was well defined, occurring once a year during April and early May. Peaks in spawning occurred after the full and new moons and was completed within a single lunar cycle. The presence of mature males over the entire size and age range and the absence of inactive mature females during the spawning season suggested that the population was not constrained by sperm limitation. While specimens undergoing sexual transition were only observed in size and age ranges of 335–685 mm total length ( L T ) and 5–6 years, patterns in the proportion of males in size and age classes suggested that sex change occurred at a relatively constant rate after female maturation up to the maximum size (1002 mm L T ) and age (11 years). Relationships between reproductive output and capacity with size and age indicated that conventional regulations that equate the mean size at first capture to sexual maturation are unsuitable for the management of E. coioides . The maximum age, small size and young age at sexual maturation ( L min = 320 mm L T , 2 years, for females and 242 mm L T , 1 year, for males) conflict with the general pattern for large epinepheline groupers and may be a direct result of the intensive demersal fishery in the southern Arabian Gulf.

Quasi periodicities of extreme precipitation events in the Yangtze River basin, China - S. Becker; H. Hartmann; M. Coulibaly; Q. Zhang; T. Jiang (Theoretical and Applied Climatology, 2008)

Pharmacological modulation of the neural basis underlying inhibition of return (IOR) in the human 5-HT2A agonist and NMDA antagonist model of psychosis - Jörg Daumann; Karsten Heekeren; Anna Neukirch; Christiane M. Thiel; Walter Möller-Hartmann; Euphrosyne Gouzoulis-Mayfrank (Psychopharmacology, 2008)

Effects of age on neuromuscular knee joint control - M. Melnyk; F. v. Luebken; J. Hartmann; L. Claes; A. Gollhofer; B. Friemert (European Journal of Applied Physiology, 2008)

Characterisation of the nascent polypeptide-associated complex in fission yeast - Katrine M. Andersen; Colin A. Semple; Rasmus Hartmann-Petersen (Molecular Biology Reports, 2007)

Detection of Pathogenic Yersinia enterocolitica in Meat using Real-Time PCR - M. Fredriksson-Ahomaa; B. Hartmann; P. Scheu; A. Stolle (Journal of Consumer Protection and Food Safety, 2007)

Identification of nestin-positive putative mammary stem cells in human breastmilk - Mark D. Cregan; Yiping Fan; Amber Appelbee; Mark L. Brown; Borut Klopcic; John Koppen; Leon R. Mitoulas; Kristin M. E. Piper; Mahesh A Choolani; Yap-Seng Chong; Peter E. Hartmann (Cell and Tissue Research, 2007)

Quantitative diffusion tensor imaging in herpes simplex virus encephalitis - C Herweh; MR Jayachandra; M Hartmann; A Gass; J Sellner; S Heiland; S Nagel; St Hähnel; U Meyding-Lamadé (Journal of NeuroVirology, 2007)

Blockade and enhancement of glutamate receptor responses in Xenopus oocytes by methylated arsenicals - Katharina Krüger; Janina Gruner; Michael Madeja; Louise M. Hartmann; Alfred V. Hirner; Norbert Binding; Ulrich Mußhoff (Archives of Toxicology, 2006)

Expression analysis of the AtMLO Gene Family Encoding Plant-Specific Seven-Transmembrane Domain Proteins - Zhongying Chen; H. Andreas Hartmann; Ming-Jing Wu; Erin J. Friedman; Jin-Gui Chen; Matthew Pulley; Paul Schulze-Lefert; Ralph Panstruga; Alan M. Jones (Plant Molecular Biology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

Phytochrome-mediated long-term memory of seeds - K. M. Hartmann; A. C. Grundy; R. Market (Protoplasma, 2005)

Occurrence and distribution of endobacteria in the plant‐associated mycelium of the ectomycorrhizal fungus Laccaria bicolor S238N - J. Bertaux; M. Schmid; P. Hutzler; A. Hartmann; J. Garbaye; P. Frey‐Klett (Environmental Microbiology, 2005)
Summary Fluorescence in situ hybridization, associated with confocal laser scanning microscopy or epifluorescence microscopy with deconvolution system, has allowed the detection of a community of intracellular bacteria in non‐axenic samples of the ectomycorrhizal fungus Laccaria bicolor S238N. The endobacteria, mainly α‐proteobacteria, were present in more than half of the samples, which consisted of ectomycorrhizae, fungal mats and fruit bodies, collected in the glasshouse or in the forest. Acridine orange staining suggests that the endobacteria inhabit both live and dead fungal cells. The role of these endobacteria remains to be clarified.

Potential climatic effects of cirrus contrails for the subarctic setting of Fairbanks, Alaska - G. Wendler; M. Shulski; B. Hartmann (Theoretical and Applied Climatology, 2005)

Effect of glucocorticoïd receptor ligands on myosin heavy chains expression in rat skeletal muscles during controllable stress - J. M. Martrette; N. Hartmann; A. Westphal; L. Favot (Journal of Muscle Research and Cell Motility, 2004)

Acquired and Partially De Novo Synthesized Pyrrolizidine Alkaloids in Two Polyphagous Arctiids and the Alkaloid Profiles of Their Larval Food-Plants - T. Hartmann; C. Theuring; T. Beuerle; L. Ernst; M. S. Singer; E. A. Bernays (Journal of Chemical Ecology, 2004)

Atomic force microscopy and scanning near-field optical microscopy studies on the characterization of human metaphase chromosomes - M. Oberringer; A. Englisch; B. Heinz; H. Gao; T. Martin; U. Hartmann (European Biophysics Journal, 2003)

Experience influences gustatory responsiveness to pyrrolizidine alkaloids in the polyphagous caterpillar, Estigmene acrea - R. F. Chapman; E. A. Bernays; M. S. Singer; T. Hartmann (Journal of Comparative Physiology A, 2003)

Influence of arsenic on antimony methylation by the aerobic yeast Cryptococcus humicolus - Louise M. Hartmann; Peter J. Craig; Richard O. Jenkins (Archives of Microbiology, 2003)

R 56865 exerts cardioprotective properties independent of the intracellular Na + -overload in the guinea pig heart - Matthias Hartmann; Ulrich K. M. Decking (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Colonization of pepper roots by a plant growth promoting Pseudomonas fluorescens strain - J. A. Lucas García; M. Schloter; T. Durkaya; A. Hartmann; F. J. Gutiérrez Mañero (Biology and Fertility of Soils, 2003)

Sequestration and Metabolism of Protoxic Pyrrolizidine Alkaloids by Larvae of the Leaf Beetle Platyphora boucardi and Their Transfer via Pupae into Defensive Secretions of Adults - Jacques M. Pasteels; Claudine Theuring; Ludger Witte; Thomas Hartmann (Journal of Chemical Ecology, 2003)

An in silico central pattern generator: silicon oscillator, coupling, entrainment, and physical computation - M. Anthony Lewis; Ralph Etienne-Cummings; Mitra J. Hartmann; Zi Rong Xu; Avis H. Cohen (Biological Cybernetics, 2003)

Effect of humidity on cuticular water permeability of isolated cuticular membranes and leaf disks - L. Schreiber; M. Skrabs; K. Hartmann; P. Diamantopoulos; E. Simanova; J. Santrucek (Planta, 2001)

A mitochondrial molecular marker of resistance to Bayoud disease in date palm - B. Quenzar; M. Trifi; B. Bouachrine; C. Hartmann; M. Marrakchi; A. A. Benslimane; A. Rode (Theoretical and Applied Genetics, 2001)

Feasibility and potential gains of enhancing the subacute rat study protocol (OECD test guideline no. 407) by additional parameters selected to determine endocrine modulation. A pre-validation study to determine endocrine-mediated effects of the antiandrogenic drug flutamide - P. Andrews; A. Freyberger; E. Hartmann; R. Eiben; I. Loof; U. Schmidt; M. Temerowski; M. Becka (Archives of Toxicology, 2001)

The action spectrum for maximal photosensitivity of germination - K. M. Hartmann; A. Mollwo (The Science of Nature, 2000)

Pharmacology of a selective cyclooxygenase-2 inhibitor, HN-56249: a novel compound exhibiting a marked preference for the human enzyme in intact cells - J. Berg; H. Fellier; T. Christoph; P. Kremminger; M. Hartmann; H. Blaschke; F. Rovensky; R. Towart; D. Stimmeder (Naunyn-Schmiedeberg's Archives of Pharmacology, 2000)

Sequestration, Maintenance, and Tissue Distribution of Pyrrolizidine Alkaloid N-Oxides in Larvae of Two Oreina Species - Adelheid Ehmke; Martine Rahier; Jacques M. Pasteels; Claudine Theuring; Thomas Hartmann (Journal of Chemical Ecology, 1999)

Primary DNA Damage But Not Mutagenicity Correlates with Ciprofloxacin Concentrations in German Hospital Wastewaters - A. Hartmann; E. M. Golet; S. Gartiser; A. C. Alder; T. Koller; R. M. Widmer (Archives of Environmental Contamination and Toxicology, 1999)

Effect of controllable stress on myosin heavy chain expression and muscle-specific protection by clomipramine - J. M. Martrette; N. Hartmann; A. Westphal; M. Divry (Journal of Muscle Research and Cell Motility, 1998)

High-resolution genetic and physical mapping of the Rar1 locus in barley - T. Lahaye; S. Hartmann; S. Töpsch; A. Freialdenhoven; M. Yano; P. Schulze-Lefert (Theoretical and Applied Genetics, 1998)

Effects of pre- and perinatal exposure to hypergravity on muscular structure development in rat - J. M. Martrette; A. Westphal; N. Hartmann; S. Vonau (Journal of Muscle Research and Cell Motility, 1998)

Characterization of the human type II Na/P i -cotransporter promoter - Helene Hilfiker; Ivica Kvietikova; Claudia M. Hartmann; Gerti Stange; H. Murer (Pflügers Archiv - European Journal of Physiology, 1998)

Tree rooting patterns and soil water relations of healthy and damaged stands of mature oak (Quercus robur L. and Quercus petraea [Matt.] Liebl.) - Frank M. Thomas; Günter Hartmann (Plant and Soil, 1998)

The two 3-deoxy- d - arabino -heptulosonate-7-phosphate synthase isoenzymes from Saccharomyces cerevisiae show different kinetic modes of inhibition - Georg Schnappauf; Markus Hartmann; M. Künzler; G. H. Braus (Archives of Microbiology, 1998)

C-met activation is necessary but not sufficient for liver colonization by B16 murine melanoma cells - Shuo Lin; Dario Rusciano; Patrizia Lorenzoni; Guido Hartmann; Walter Birchmeier; Silvia Giordano; Paolo Comoglio; Max M. Burger (Clinical & Experimental Metastasis, 1998)

Identification of UV/blue light-response elements in the Arabidopsis thaliana chalcone synthase promoter using a homologous protoplast transient expression system - Ulrike Hartmann; William J. Valentine; John M. Christie; John Hays; Gareth I. Jenkins; Bernd Weisshaar (Plant Molecular Biology, 1998)

Raynaud's phenomenon and acral necrosis after chemotherapy for AIDS-related Kaposi's sarcoma - M. Reiser; C. Bruns; P. Hartmann; B. Salzberger; V. Diehl; G. Fätkenheuer (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Major histocompatibility complex (MHC) class III genetics in two Amerindian tribes from Southern Brazil: the Kaingang and the Guarani - S. Weg-Remers; M. Brenden; E. Schwarz; K. Witzel; P. M. Schneider; L. K. Guerra; I. R. Rehfeldt; M. T. Lima; D. Hartmann; M. L. Petzl-Erler; I. J. T. de Messias; G. Mauff (Human Genetics, 1997)

Evaluation of commercial soybean inoculants from Argentina - M. Gomez; N. Silva; A. Hartmann; M. Sagardoy; G. Catroux (World Journal of Microbiology and Biotechnology, 1997)

Reproductive toxicity and toxicokinetics of 2,3,7,8-tetrachlorodibenzo-p-dioxin - Ibrahim Chahoud; Jutta Hartmann; Gabriele M. Rune; Diether Neubert (Archives of Toxicology, 1992)

Components and mechanism of protein translocation across the ER membrane - Tom A. Rapoport; Dirk Grlich; Anne Msch; Enne Hartmann; Siegfried Prehn; Martin Wiedmann; Albrecht Otto; Susanne Kostka; Regine Kraft (Antonie van Leeuwenhoek, 1992)